Biological control of diseases caused by Rhizoctonia solani AG-2-2 in sugar beet (Beta vulgaris L.) using plant growth-promoting rhizobacteria (PGPR). (March 2023) - Farhaoui, Abdelaaziz; El Alami, Nabila; Khadiri, Mohammed; Ezrari, Said; Radouane, Nabil; Baala, Mohammed; Tahiri, Abdessalem; Lahlali, Rachid
Abstract: The soil-borne pathogen Rhizoctonia solani AG-2-2 induces both root and crown rot (RCR) and damping-off in sugar beet, which considerably reduces the productivity of this industrial crop. Most often, synthetic fungicides are commonly used to control this fungus. Biological control agents have attracted interest as an alternative to chemical fungicides for controlling several plant diseases. The current study aimed at finding antagonistic bacteria that could be used for biological control against this pathogen. A set of 198 bacterial strains were screened using an in vitro dual culture test with R. solani AG-2-2. Out of these, eleven isolates with important antifungal activity against the pathogen were chosen and characterized using 16S rRNA gene sequencing. Molecular characterization demonstrated that all selected isolates clustered under the genus Bacillus ( B. velezensis B. amyloliquefaciens and B. subtilis ). In addition, chosen isolates of bacteria were also characterized for their potential to synthesize antifungal metabolites and for their abilities as plant growth-stimulators. Bacterial isolates differed substantially in their capability to synthesize antifungal metabolites and for their abilities as plant growth-stimulators. Bacterial isolates differed substantially in their capability to synthesize antifungal metabolites and for their abilities as plant growth-stimulators. Bacterial isolates differed substantially in their capability to synthesize lipopeptide antibiotics. A test under greenhouse conditions revealed that sugar beet seeds soaked in an individual bacterial isolate significantly decreased Rhizoctonia damping-off. Additionally, seedlings grown from soaked seeds exhibited significant increase in assessed growth parameters. Likewise, selected bacterial isolates exhibited an antagonistic effect on this pathogen, and considerably decreased the severity of RCR caused by Rhizoctonia . For sustainable agriculture, B. velezensis SS2 seems more promising as a fungal biocontrol agent against Rhizoctonia RCR and B. velezensis BM2 can be used as a bio-fertilizer. Highlights: Eleven antagonistic bacteria showing an inhibition rate greater than 50% against of Rhizoctonia solani were selected. Bacterial isolates displayed their ability to synthesize antibiotic lipopeptides and extracellular enzymes with PGPR effect. Under greenhouse conditions, sugar beet treated with an individual bacterial isolate displayed significant reduction of diseases caused by R. solani . Plants grown from seeds soaked with one of the bacteria evaluated exhibited a significant increase in plant growth . Selected antagonistic bacteria significantly decreased the incidence and severity of diseases and B. velezensis strain SS2 was the most promising bacterium.